The enchanted : a novel - Denfeld, Rene (Harper, 2014)
The enchanted place is an ancient stone prison, viewed through the eyes of a death row inmate who finds escape in his books and in re-imagining life around him. A female investigator searches for buried information from prisoners' pasts that can save those soon-to-be-executed. Digging into the background of a killer named York, she uncovers wrenching truths that challenge familiar notions of victim and criminal, innocence and guilt, and reveals shocking secrets of her own.